Tasting Heaven on Earth: Worship in Sixth-Century Constantinople - Plekon, Michael (Cistercian studies quarterly, 2013)
The article reviews the book "Tasting Heaven on Earth: Worship in Sixth-Century Constantinople," by Walter D. Ray.